Aspartate Aminotransferase to Platelet Ratio Index and FibroScan for Predicting Liver Fibrosis with Chronic Hepatitis B - Tarigan, Elias; Yusuf, Rustam Effendi; Dairy, Leonardo Basa; Sembiring, Juwita; Sihombing, Mabel HM; Siregar, Gontar Alamsyah; Zain, Lukman Hakim (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2013)
Background: Non-invasive test have been constructed and evaluated mainly for binary diagnoses. The accuracy of non-invasive tests such as aspartate aminotransferase to platelet ratio index (APRI) and transientelastography/FibroScan should be evaluated especially in clinical practice. The aim of the study was to evaluate the accuracy of detailed fibrosis classification available for APRI and FibroScan to liver biopsy in chronichepatitis B patients.Method: A cross sectional study was conducted in 51 patients with chronic hepatitis B. The patients underwent laboratory test, FibroScan and liver biopsy between April 2011 and July 2013 at Adam Malik Hospital, Medan.Liver biopsy was assessed based on the METAVIR score. Area under receiver operating characteristic curve (AUROC) predictive value was used to evaluate the accuracy of APRI and FibroScan. All data were analyzedusing SPSS 20.0.Results: APRI versus METAVIR diagnosed severe fibrosis and cirrhosis with sensitivity 40% and specificity 83.9%, positive predictive value (PPV) 61.5%, negative predictive value (NPV) 68.4%, positive likelihood ratio(LR) 2.48 and negative LR 0.72 with diagnostic accuracy 66.7%. The AUROC value was 0.619 (95% CI = 0.446 – 0.715); kappa = 0.255; p 0.05. FibroScan versus METAVIR predictive value with sensitivity 75% andspecificity 67.6% were PPV 60%, NPV 67.7%, positive LR 2.31 and negative LR 0.36 with diagnostic accuracy 70.6%. The AUROC value was 0.714 (95% CI = 0.567–0.861); kappa 0.409; p 0.05.Conclusion: FibroScan has better accuracy than APRI for predicting severe fibrosis and cirrhosis in patientswith chronic hepatitis B.Keywords: APRI, FibroScan, liver biopsy, chronic hepatitis B